Understanding shading through home-use experience, measurement and modelling - Magdalena Baborska-Narożny; Karol Bandurski; Magdalena Grudzińska (Buildings & Cities)
Insufficient application of the socio-technical influences on residential energy ‘optimisation’ exacerbates the energy performance gap. This is evident in the modelling of energy and thermal performance. Shading control has the potential to optimise energy demand. This research explores inhabitants’ shading practices across the seasons in occupied low-energy homes. It identifies, describes and quantifies the contextual drivers that underpin individual preferences and triggers for shading activity and their impact on the thermal–energy nexus. In-depth building performance evaluations of five homes built to the same specifications were used to inform dynamic thermal modelling. Simulation scenarios were developed based on inhabitants’ lived experiences. A comparison of two airflow network modelling approaches was conducted, and tailored shading usage models were compared with a default TRNSYS model. A calibrated simulation, representing observed shading practices, quantified the impacts on heating energy and overheating mitigation. The process and findings can be used to improve modelling approaches by reflecting inhabitants’ actual experiences and informing decisions about shading strategies. These findings challenge the current approach used in energy codes and static models which use values based on average inhabitant practices. More appropriate tools with increased sensitivity are needed to account for varied and alternative usage scenarios and assumptions. Practice relevance Window treatments that enable shading control in housing are typically considered an interior design feature, beyond the scope of building design and construction. The significant impact of shading on annual energy balance needs attention as a design issue. Passive and active measures (curtains, blinds, shutters, window opening, etc.) need consideration at the design stage, and particularly in modelling. This study demonstrates why practitioners should aim to better understand and account for the variability of user actions involving the use of shading and window opening. In terms of policy, energy codes should prescribe shading options in new dwellings. This would help to limit the proliferation of energy-consuming technologies such as air-conditioning.